A comparison of the diagnostic accuracy of the AD8 and BCAT-SF in identifying dementia and mild cognitive impairment in long-term care residents. Issue 5 (2nd September 2016) - Mansbach, William E.; Mace, Ryan A.
ABSTRACT: We compared the accuracy of the Brief Cognitive Assessment Tool—Short Form (BCAT-SF) and AD8 in identifying mild cognitive impairment (MCI) and dementia among long-term care residents. Psychometric analyses of 357 long-term care residents ( n = 228, nursing home; n = 129, assisted living) in Maryland referred for neuropsychological evaluation evidenced robust internal consistency reliability and construct validity for the BCAT-SF. Furthermore, hierarchical logistic regression and receiver operating characteristic curve analyses demonstrated superior predictive validity for the BCAT-SF in identifying MCI and dementia relative to the AD8. In contrast, previously reported psychometric properties or cut scores for the AD8 could not be cross-validated in this long-term care sample. Based on these findings, the BCAT-SF appears to be a more reliable and valid screening instrument than the AD8 for rapidly identifying MCI and dementia in long-term care residents.